Dimeric hexylitaconic acids from the marine-derived fungus Aspergillus welwitschiae CUGBMF180262. Issue 2 (17th January 2022) - Han, Jiahui; Yang, Na; Wei, Shangzhu; Jia, Jia; Lin, Rui; Li, Jiangpeng; Bi, Hongkai; Song, Fuhang; Xu, Xiuli
Abstract: In the course of our efforts to search new secondary metabolites from marine-derived fungi, one new hexylitaconic acid derivative, 3-(5-methoxycarbonylpentyl)-4-methylfuran-2, 5-dione (1 ), and two dimeric analogues asperwelwinates A and B (2 and 3 ), together with ten known compounds, asperitaconic acid C (4 ), kotanin (5 ) and orlandin (6 ), desertorin B (7 ), fonsecinone A (8 ), aurasperone A (9 ), asperpyrones B and C (10 a nd 11 ), aspernigrin B (12 ), and pyrophen (13 ), were isolated from a strain of Aspergillus welwitschiae CUGBMF180262. The structures of compounds 1–3 were determined by detailed analysis of HRMS, and 1D/2D NMR experiments, while the absolute configurations of 2 and 3 were determined by comparison of experimental and calculated electronic circular dichroism spectra. 2 and 3 were first reported dimeric hexylitaconic acid derivatives. Compounds 8, 9 and 11 showed moderate antibacterial activities against Helicobacter pylori with minimum inhibitory concentration (MIC) values of 16 μg/mL. Graphical Abstract: UF0001